Society attitudes towards the Human Rights of homeless people who consume the socalled drug “H”, in the canton of La Libertad (Ecuador) during Covid-19 times - Cevallos Mora , Francia; Guale Sánchez , Andrea; Idrobo Narváez , Ivette; Apolinario Suárez, Gino (Revista Universidad de Guayaquil, 2020)
The global COVID-19 pandemic has deeply transformed our societies in every aspect, highlyimpacting the lives of people who live under poverty lines. In Ecuador the scenario hasworsened for vulnerable populations, even though the legal Constitution establishes the rightsof personal integrity, people living on the streets have been left behind. In the Canton LaLibertad, the prevalence rate of the consumption of the so-called drug "H" has increased dueto the use of it by homeless located in the area of the Seafood Market-Calle Zona H.The need to carry out an analysis of the situation has been identified as a response to the Covid19 health emergency. The study has shown the vulnerability in which they live as well as thelack of access to guarantee of their rights as stated in the Constitution.This has led them to higher poverty rates and unemployment, instability, lack of access tohealth services, violence, and problematic dependence on alcohol and harmful substances.Therefore, this analysis exposes the need of a comprehensive protection system, with anapproach and care to all its particularities, developed in a multidimensional way from theHuman Rights perspective.
Keywords: Human Rights; Covid-19; Violence; Drugs; Society; Human Beings; Street Situation; Ecuador